2015
DOI: 10.1097/ijg.0b013e31829d9b41
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Fixation Stability During RareBit Perimetry and Humphrey Visual Field Testing

Abstract: Use of the RBP kinetic fixation target is associated with consistent fixation stability and decreased fixation loss compared with the HVF static target. This improvement in fixation stability may result from decreased perception interference (Ganzfeld, Troxler, and binocular rivalry effects), and may help account for the greater comfort reported with RBP compared with HVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Although the wearable eye-tracking glasses had the same sampling rate of 30 Hz in our study and in the study by Lin at al. [22], the fixation behavior in the current study (0.4° to 0.6°) was lower than that obtained in the study by Lin and colleagues. The difference in the results might be due to the fact that the student volunteers recruited in the current study had adequate understanding of and experience undergoing the visual field test.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Although the wearable eye-tracking glasses had the same sampling rate of 30 Hz in our study and in the study by Lin at al. [22], the fixation behavior in the current study (0.4° to 0.6°) was lower than that obtained in the study by Lin and colleagues. The difference in the results might be due to the fact that the student volunteers recruited in the current study had adequate understanding of and experience undergoing the visual field test.…”
Section: Discussioncontrasting
confidence: 94%
“…A study of 14 healthy participants by Lin et al [22] reported that fixation behavior during Humphrey SAP 10–2 with Point fixation targets (approximately 1.1°) had a mean of 2.9°. Although the wearable eye-tracking glasses had the same sampling rate of 30 Hz in our study and in the study by Lin at al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that fixation disturbances during visual field testing increase with increasing target size 35 36 , in glaucoma patients 37 , and with increasing magnitude of the visual field defect 38 . It has also been reported that slight fixation disturbances of approximately 2.9° can occur during reliable visual field testing 39 and that fixation disturbances of <2.5° occur in up to 60% of reliable visual field tests 40 . Additionally, ganglion cells are most heavily concentrated in the macular area, and ganglion cell density decreases as eccentricity increases 41 .…”
Section: Discussionmentioning
confidence: 95%
“…29 In addition, other studies have reported fixation behavior of 0.43° to 2.9° during SAP. 30,31 It is thought that fixation behavior during VF measurement affects the repeatability of each test point in patients with early and moderate glaucoma, who exhibit normal and relatively defective areas.…”
Section: Discussionmentioning
confidence: 99%